The ASMBS textbook of bariatric surgery : Volume 2: integrated health - Sarwer, David B.; Blankenship, Jeanne; Still, Christopher (Springer New York, 2014)
Developed by the American Society for Metabolic and Bariatric Surgery (ASMBS), The ASMBS Textbook of Bariatric Surgery provides a comprehensive guide of information dealing with the ever evolving field of bariatric surgery.     Volume II: Integrated Health is divided into 3 sections: bariatric medicine, psychosocial, and nutritional aspects of bariatric surgery. The first section deals with the psychosocial issues associated with severe obesity. The second section deals with the role of obesity medicine physicians in preoperative and postoperative support of the bariatric patients. The nutritional section discusses the preoperative and postoperative nutritional support for the bariatric patient.       The ASMBS Textbook of Bariatric Surgery, Volume II: Integrated Health is of great value to surgeons, residents and fellows, obesity medicine physicians, psychologists, psychiatrists, and integrated health members that manage patient affected by the disease of obesity.